The Rohingya refugees in Bangladesh: a difficult path to integration, between humanitarian and security concerns - Parven, Shahanaz (2021)
In this paper, we analyse the tensions between the promotion of human rights for the Rohingya refugees in Bangladesh and the security of the country against the risk of civil war. Under the theoretical framework of ethnopolitical conflicts, and the methodology of the four factors model, we develop a risk assessment for a civil conflict in Bangladesh based upon behaviouristic observables. The assessment suggests that some human rights would, if promoted, increase the factors of risk for civil war in the host country. In particular, solving the problem of statelessness of the refugees through their political integration in the host country is linked to an increase in the risk of civil conflict. The promotion of other rights, such as access to health and the right to repatriation, seems to decrease the level of risk of conflict. This lets us formulate the desirable chracteristics of a policy for integration that does not worsen the political instability of the country. The implications of this study in light of the illegal acquisition of Bangladeshi passports by some Rohingya refugees are also discussed.